Penyuluhan Pemanfaatan Lemak Kakao untuk Pembuatan Sabun Padat - Anggreni , Salcy; Wahyuni, Yuyun; Heliana, Almaria (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Cocoa butter is a by-product in the production process of chocolate bars and chocolate powder. In Bloro Village, Nita District, Sikka Regency, cocoa butter is produced in quite significant quantities, considering that Bloro Village is one of the largest cocoa producers in Sikka. The "Plea Puli" farming group in the village manages a production house known as "Plea Puli Chocolate House." The main objective of this research is to use cocoa butter produced from the chocolate production process as a basic ingredient for making bar soap. Soap is a chemical compound made through the reaction between fat or oil and alkali (usually sodium hydroxide). This soap has emulsifying properties that allow it to bind with dirt and oil on the skin, which can then be washed away. Therefore, the cocoa butter produced from the chocolate production process can be an absorbing soap-making base material. By using these tallow cocoa stalks to make soap, we can create added value for chocolate by-products, which have been considered waste. Apart from that, this can also make a real contribution to local economic development by helping to increase the income of cocoa farmers and encouraging the growth of the Plea Puli Farmers Group.